A Fluorescent Polyurethane with Covalently Cross-Linked Rhodamine Derivatives - Saiqi Tian (Polymers, 2020)
Rhodamine derivatives (RDs) with three reactive hydrogens were synthesized and well characterized by Fourier transform infra-red spectroscopy (FTIR), 1H nuclear magnetic resonance (1H NMR) and electrospray ionization mass spectra (ESI mass). Then, the obtained RD was covalently cross-linked into polyurethane (PU) matrix through chemical linkages to fabricate a network structure, and the fluorescent properties, mechanical properties, thermal stability, and emulsion particle size were systematically investigated. Results demonstrate that PU-RD maintains initial fluorescent properties and emits desirable yellow fluorescence under ultraviolet irradiation. Moreover, compared with linear PU without fluorescers, PU-RD shows clearly improved mechanical properties and thermal stability, on account of the formed network structures.